Physical Activity Correlates in Persons with Binge Eating Disorder: A Systematic Review. (9th September 2013) - Vancampfort, Davy; Vanderlinden, Johan; Stubbs, Brendon; Soundy, Andrew; Pieters, Guido; Hert, Marc De; Probst, Michel
Abstract Understanding the factors that influence physical activity in persons with binge eating disorders can aid the design of more effective interventions. In order to address this, the present paper provides a systematic quantitative review of the correlates of physical activity in people with binge eating disorder. We searched PsycINFO, PubMed and PEDro from inception until June 2013. Keywords included 'binge eating' with 'physical activity' or 'exercise', or 'physical inactivity' or 'sedentary'. Nine papers involving 636 (489 women) persons with binge eating disorders and evaluating 24 correlates were included. No consistent physical activity correlates were reported in four or more studies. The only significant correlate with lower physical activity participation reported in more than one study was a negative body attitude. Further research is required to address this current gap in literature. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.